2019
DOI: 10.1097/iae.0000000000001917
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Efficacy of Intravitreal Bevacizumab Injection for Chronic, Atypical, or Recurrent Central Serous Chorioretinopathy

Abstract: As-needed optical coherence tomography-based IVB was effective for reducing CRT in patients with chronic, atypical, or recurrent CSC, and for vision improvement in chronic and recurrent CSC over the 1-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…In addition, Spearman's rank correlation coefficient clearly indicated the presence of significant correlations among the angiogenic cytokines in the chronic CSC group, whereas the correlations among these cytokines in the acute CSC groups were significantly lower. Anti-VEGF therapy has been reported as an effective treatment for chronic CSC 44,45 and PNV. 27,46 The gradual increase of VEGF and PlGF along with disease progression may suggest that CNV arises as a consequence of angiogenic cytokine accumulation, triggered by aberrant interaction between dysregulated RPE and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Spearman's rank correlation coefficient clearly indicated the presence of significant correlations among the angiogenic cytokines in the chronic CSC group, whereas the correlations among these cytokines in the acute CSC groups were significantly lower. Anti-VEGF therapy has been reported as an effective treatment for chronic CSC 44,45 and PNV. 27,46 The gradual increase of VEGF and PlGF along with disease progression may suggest that CNV arises as a consequence of angiogenic cytokine accumulation, triggered by aberrant interaction between dysregulated RPE and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In the retrospective study, Chung et al. evaluated the efficacy of IVB injection in the treatment of 77 eyes from 71 patients with chronic, atypical, or recurrent CSC 36 . They injected IVB in 6-week intervals until SRF absorption and then based on an as-needed protocol according to OCT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, retrospective evaluation of intravitreal bevacizumab treatment in patients with chronic and recurrent CSC (77 eyes of 71 patients) showed reduction in central retinal thickness and associated improved visual acuity. [ 38 ] However, a randomised controlled trial of 32 eyes of 34 patients comparing ranibizumab and half-fluence PDT in patients with chronic CSC suggested that PDT treatment was superior (in both resolution of subretinal fluid and improvement in visual acuity). [ 39 ]…”
Section: Treatment Strategies For Central Serous Chorioretinopathymentioning
confidence: 99%
“…[ 43 ] Furthermore, a recent retrospective study evaluating patients with chronic or recurrent CSC showed that intravitreal bevacizumab was useful in reduced in choroidal thickness and improving visual outcomes at 1 year. [ 38 ] These studies have promising results for anti-VEGF treatment in CSC, although it would be useful to also exclude concurrent CNV with OCTA.…”
Section: Treatment Strategies For Central Serous Chorioretinopathymentioning
confidence: 99%